2016
DOI: 10.1002/ppsc.201600016
|View full text |Cite
|
Sign up to set email alerts
|

Structures, Oxidation, and Charge Transport of Phosphorus‐Doped Germanium Nanocrystals

Abstract: The doping of semiconductor nanocrystals (NCs) is crucial for the optimization of the performance of devices based on them. In contrast to recent progress on the doping of compound semiconductor NCs and silicon NCs, the doping of germanium (Ge) NCs has lagged behind. Here it is shown that Ge NCs can be doped with phosphorus (P) during synthesis by a nonthermal plasma. It is found that there are more P atoms in the NC near‐surface region than in the NC core. P doping modifies the surface state of Ge NCs. Compre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
21
1
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 52 publications
(82 reference statements)
1
21
1
1
Order By: Relevance
“…It was interesting to find that Hall mobilities were significantly increased from 0.14 cm 2 /V⋅s for the as-deposited film to 182 cm 2 /V⋅s for the Ge NCs film annealed at 500 ∘ C, which are improved more than three orders of magnitude after annealing. Compared with any other work investigating the electronic properties of Ge NCs, our values of Hall mobility are more outstanding than those of previous reports [24,25]. It is well known that the enhanced Hall mobility after annealing is actually attributed to the formation of Ge NCs in the films [12].…”
Section: Resultscontrasting
confidence: 59%
“…It was interesting to find that Hall mobilities were significantly increased from 0.14 cm 2 /V⋅s for the as-deposited film to 182 cm 2 /V⋅s for the Ge NCs film annealed at 500 ∘ C, which are improved more than three orders of magnitude after annealing. Compared with any other work investigating the electronic properties of Ge NCs, our values of Hall mobility are more outstanding than those of previous reports [24,25]. It is well known that the enhanced Hall mobility after annealing is actually attributed to the formation of Ge NCs in the films [12].…”
Section: Resultscontrasting
confidence: 59%
“…В то время как HК Si изучены достаточно полно, гораздо меньше работ было посвящено исследованию НК Ge [16][17][18][19][20][21][22][23][24][25], либо НК Ge x Si 1−x , встроенных в диэлектрические матрицы [26][27][28][29][30][31][32], или исследованию нанопорошков Ge x Si 1−x [33,34]. Стоит отметить, что НК Ge имеют ряд преимуществ.…”
Section: Introductionunclassified
“…[36][37][38][39][40] It is only recently that Ge QDs have been doped with boron (B) and phosphorus (P) by using a gas-phase synthesis approach. 41,42 It is found that both B and P atoms prefer occupying the near-surface region of Ge QDs, rather than the core of the QDs. The conductivity of Ge-QD lms may be effectively modulated by the doping of Ge QDs with B and P. 41,42 It is well known that theoretical simulation is critical to understanding on the doping mechanism of semiconductor QDs.…”
Section: Introductionmentioning
confidence: 99%
“…41,42 It is found that both B and P atoms prefer occupying the near-surface region of Ge QDs, rather than the core of the QDs. The conductivity of Ge-QD lms may be effectively modulated by the doping of Ge QDs with B and P. 41,42 It is well known that theoretical simulation is critical to understanding on the doping mechanism of semiconductor QDs. As a powerful theory for the investigation on the structural and electronic properties of materials, density functional theory (DFT) has been extensively employed to study the doping of a variety of semiconductor QDs such as the group IV counterpart of Ge QDs-silicon (Si) QDs.…”
Section: Introductionmentioning
confidence: 99%